Pemanfaatan PLTS Sebagai Sumber Energi Pengendalian Suhu Ruangan Berbasis Arduino - Maulana, Farhan Eka; Ariwibowo, Moh. Mukti; Abadi, Moh. Fairus; Hadiyansyah; Fillabda, Nadia Aden (CV. SINAR HOWUHOWU, 2025)
The issues of energy crisis and global warming have driven innovation in the development of environmentally friendly and energy-efficient technologies. One promising solution is the utilization of Solar Power Plants (PLTS) as a renewable energy source for small-scale electricity needs, such as in room temperature control systems. This study aims to design and implement a room temperature control system based on Arduino, which is fully powered by energy from PLTS. The system operates by reading the room temperature using a DHT22 temperature sensor, and then automatically activates a fan or cooling device according to predetermined temperature thresholds. All the energy used in this system is supplied by solar panels connected to an energy storage and conversion system. Testing results show that the system functions effectively in maintaining room temperature within a comfortable range and is capable of operating independently without relying on the conventional power grid. The use of PLTS in this system not only provides energy efficiency but also contributes to environmental conservation efforts by reducing carbon emissions.